Gestational and lactational exposition to di-n-butyl phthalate increases neurobehavioral perturbations in rats: A three generational comparative study - P, Mahaboob Basha; M.J., Radha (Toxicology reports, 2020)
[Display omitted] •DBP intoxicated F3 progeny scored low in sensorimotor-indices than F1 and F2.•A higher behavioural discrepancy in F3 progeny and subjects committed more errors.•Correlates between hormonal milieu and behavioural indices signify vulnerability of developing animals.•Deceptive cholinergic functionary was apparent in experimental rats.•Marked neuronal degeneration in CA1 and CA3 and severe hyperplasia in the dentate gyrus region were evident. Di-n-butyl phthalate (DBP) cause significant deficits in cognition and memory, however the neuroanatomical basis for impairments remain poorly understood. This study evaluates neurobehavioral changes in rats for three successive generations between non-siblings by administering DBP at 500mg/kg bw dose through oral gavage from gestation day-6 to 21 and lactation (3-weeks). Weaning period evaluations and developmental deficits assessed showed variations specific to generation and the toxic potential of DBP was confounded by behavioral deficits that include changes in sensorimotor development reflex response, poor performance, low memory retention and greater latency period. The cytoarchitectural alterations witnessed in hippocampus include condensed nuclei, vacuole formation and remarkable degeneration, shrinkage of pyramidal neurons in CA1 and CA3 regions; disorganized hilar cells and hyperplasia in dentate gyrus. Comparatively, the enlisted changes were high in subsequent generations than preceding and correlates assessed between cognitive impairment(s) and endocrine function confirm a link indicating vulnerability of immature animals as target to disrupt neural and endocrine functions.